Agent-based simulation study for improving logistic warehouse performance. Issue 1 (2nd January 2018) - Ribino, Patrizia; Cossentino, Massimo; Lodato, Carmelo; Lopes, Salvatore
Abstract: Logistic warehouses are critical nodes in a supply chain and improving their performance is a crucial issue when trying to avoid unproductive bottlenecks. Warehouse optimization involves several problems, some of which must be considered at the design stage and others during real-time operations. In this study, we performed an agent-based simulation to analyze the behavior of automatic logistic warehouses under the influence of specific factors, thereby obtaining indicators to supporting decision making during warehouse performance improvement. This study focused mainly on automatic warehouses where goods are moved by automatic guided vehicles.